Predicting intention on safe food handling among adult consumers: a cross sectional study in Sibu district, Malaysia - Ruby, Genevie Eleanor; Ungku Zainal Abidin, Ungku Fatimah; Lihan, Samuel; Jambari, Nuzul Noorahya; Radu, Son (Elsevier, 2019)
This study employed the extended theory of planned behavior (TPB) to predict the intention of adult consumers towards safe food handling at home. A self-administered survey was distributed to a total of 623 respondents who lived in the Sibu district, Malaysia and analyzed the data using the partial least squares structural equation modeling technique. The empirical results revealed that consumers' attitude, subjective norm, and perceived behavior control were statistically significant and positively linked to the intention of safe food handling. Furthermore, the results indicated that the main predictor of consumer safe food handling intention was subjective norm. This study confirmed that food safety knowledge had a positive impact on consumer's attitude. From a practical standpoint, this study provided justification in highlighting the roles of family that encouraged consumers to perform safe food handling at home.